2012
DOI: 10.2478/v10172-011-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Soldering Conditions on Conductivity, Structure and Strength of Cu/Sn96Ag4 Solders

Abstract: In the paper the electrical properties of the Cu/Sn96Ag4 solders were studied. The studied solders were produced at 200, 220 and 250• C and within time range 3 to 90 s. Soldering temperatures were chosen to assure the best soldering conditions for the Cu/Sn96Ag4 alloy. The most appropriate temperature of 200• C is the one just above the melting point. The temperature of 250• C is the maximal one recommended by producers, which can be applied for the electronic elements during soldering. The studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The intermetallic compounds, which form between the SAC and copper base are similar to those found in the Sn-Pb/Cu connections. Also some studies are reported on intermetallic phases found in the Sn-Cu solder joints [3] and Sn-Ag [1,4,5]. Besides, various additions to the Sn-Ag alloy such as Ni, Cu, Al, Zn, Co, Sb, P and Au were studied in [6] and the interface layer is similar to that found in SnZn with additions.…”
Section: Introductionmentioning
confidence: 99%
“…The intermetallic compounds, which form between the SAC and copper base are similar to those found in the Sn-Pb/Cu connections. Also some studies are reported on intermetallic phases found in the Sn-Cu solder joints [3] and Sn-Ag [1,4,5]. Besides, various additions to the Sn-Ag alloy such as Ni, Cu, Al, Zn, Co, Sb, P and Au were studied in [6] and the interface layer is similar to that found in SnZn with additions.…”
Section: Introductionmentioning
confidence: 99%
“…They are expected to offer a high resistance to wear caused by [10]. Silver-nickel electrical contacts are also resistant to oxidation and corrosion, and behave well at elevated temperatures [11,12]. Due to high oxidation resistance, they are used in the overhead circuit breakers, in industrial power relays, and in various switches, stress controls, cameras and instruments, which should have high resistance to wear.…”
Section: Introductionmentioning
confidence: 99%